Seasonal modifications and morphogenesis of the hypercalcified sponge Petrobiona massiliana (Calcarea, Calcaronea) - Gilis, M.; Gosselin, P.; Dubois, P.; Willenz, P. (Invertebrate Biology, 2011)
The periodicity of sexual elements and soft tissue modifications during the life cycle of the hypercalcified sponge Petrobiona massiliana was investigated monthly from June 2006 to November 2007. Sexual reproduction, likely regulated by seawater temperatures, occurred during more than half of the year (from early April to late October); 70% of the samples appeared reproductively active. Specimens of P. massiliana displayed a high plasticity of tissue organization, allowing modulation and rearrangement of their aquiferous systems in response to life cycle phases and environmental changes. Permanent changes were observed in the basal region of the choanosome in non-reproductive specimens, such as disorganization/restructuring events leading to remodeling of the aquiferous system. Periodic modifications occurring during sexual reproduction included the transformation of choanocytes from a typical form to hourglass and vespiform shapes, and more global disorganization of the basal region of the choanosome during provisioning of oocytes and embryos, followed by restructuring after release of the larvae. Finally, episodic disorganization/reorganization phenomena occurred in a few specimens after unfavorable environmental conditions (e.g., decreasing seawater temperatures). Histological and ultrastructural observations of storage cells, located in peculiar trabecular tracts, suggest a transdifferentiation capacity that allows such soft tissue dynamics.